PEMAKNAAN GOOD CORPORATE GOVERNANCE DALAM MEWUJUDKAN TRI PANGGILAN GEREJA (BERSAKSI, BERSEKUTU, MELAYANI) - Jerliyen Pramita Londong (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2019)
The Meaning of Good Corporate Governance in manifesting Three Church Calls (Witnessing, Allying, Serving). The aims of this research determine the extent of the meaning of the application of good corporate governance in manifesting the three call of the church. Case study at the Biringkanaya’s Toraja Church by involving the representatives of church’s member in each group. This research using interpretive phenomenological analysis. The result of this study found that church program has been carried out by Biringkanaya’s Church and has adjusted to the Church’s mission, but the implementation of the program is not felt maximally by the church members.